Victorian Pornography versus Contemporary Pornography: Belinda Starling’s The Journal of Dora Damage (2008) and Women’s Agency and Emancipation. - Romero-Ruiz, María Isabel (My University, 2016)
Pornography is and has been a contentious issue in the Victorian past and in our contemporary societies, and the role of women in the business has been very much discussed by Victorian and contemporary critics and academics alike. The concern is a double-edged matter: on the one hand, we have the question of women as writers of pornography and bookbinders of pornographic books, and, on the other, their role in the pornographic market as the victims of sexual exploitation. Both issues are an important concern for the neo-Victorian agenda with the publication of historical fictions that give voice to silenced matters. These fictions also reflect the presence of pornography in our contemporary world and question our modernity and civilisation regarding sexual matters. The Diary of Dora Damage (2008) by Belinda Starling provides us with the Victorian context to analyse the role of women in the pornographic trade and to decipher all the possibilities that the business provides both for their emancipation or discrimination. Dora Damage is a woman whose husband is a bookbinder in Lambeth in the 1850s. Her husband’s illness and the threat of ending up in the workhouse make her consider the possibility of becoming a bookbinder herself. However, although she starts working with “decent material” she finds herself working for certain members of the aristocracy binding pornographic texts. In the second half of the nineteenth century pornographic books circulated among members of certain private societies like Les Sauvages Nobles who consumed these obscene publications in private circles. This led to the passing of the first Obscene Publication Act of 1857. The selling of pornographic materials became a flourishing business and Holywell Street became the centre of all kinds of transactions. The aim of this paper is to contend that Dora achieves independence and agency in a man’s world and, at the same time, re-affirms her sexual identity despite being a Victorian wife and mother. This, in the context of a Neo-Victorian novel, will also allow us to analyse how pornography is not such a liberating and emancipating activity for the women of the new millenium. At the same time, Judith Butler’s notions of a precarious life, mourning and violence will provide the theoretical framework for this paper.
Keywords: Pornografía; Starling, Belinda - Crítica e interpretación; The Diary of Dora Damage; Les Sauvages Noble; Pornography; Emancipation; Neo-Victorian